Immunogenicity of Trivalent Inactivated Influenza Vaccination Received During Pregnancy or Postpartum - Sperling, Rhoda S. (2012)
OBJECTIVE: To estimate the effects of gestational age and other maternal factors on immunologic responses to influenza vaccination. METHODS: Antepartum and postpartum women receiving influenza vaccination as part of routine clinical care were enrolled through four consecutive vaccination seasons (starting October 2006 through January 2010) Immunologic responses to trivalent inactivated influenza vaccine (TIV) and monovalent H1N1 were assessed, as well as factors influencing vaccine responsiveness. Serum samples were obtained at baseline and 4-8 weeks postvaccination. RESULTS: Two hundred thirty-nine participants were included in the current analysis. Seroconversion rates to TIV vaccine strains were lowest in the first trimester (54.8%) and immediate postpartum (54.8%), and were highest in the late third trimester (69.6%) and late postpartum (69.4%); these differences were not statistically significant (p=0.23). In a multivariable model, higher baseline antibody levels (p<.001)and prior year flu vaccination (p=0.03) were both significantly associated with reduced odds of seroconversion. Overall, results were consistent when comparing TIV and monovalent pandemic H1N1 responses. Although there was overall no significant association between gestational age at vaccination (p=0.23) or prepregnancy BMI (p=0.16), we observed somewhat lower rates of seroconversion for women vaccinated in the first trimester and for obese women. CONCLUSIONS: Adequate immunologic responses to inactivated influenza vaccines were demonstrated during pregnancy and the postpartum period. No diminution of immunogenicity was observed in the third trimester a time of increased clinical vulnerability to influenza.